Using Action Design Research for Developing and Implementing a Method for Risk Assessment and Continuity Management. (July 2022) - Cedergren, Alexander; Hassel, Henrik
Highlights: Development and implementation of a method in its naturalistic setting is outlined. The method integrates Risk Management and Business Continuity Management principles. The ADR methodology gives equal weight to practical use and scientific contribution. Data was collected through participant observation and focus group discussions. Challenges and lessons learned from this 3.5-year study are reported. Abstract: This paper presents the results from a longitudinal study aiming at developing and implementing a method integrating principles from Risk Management and Business Continuity Management in its naturalistic organisational setting. Despite the fact that a myriad of real-world constraints and challenges typically arise in the transition from method development to full implementation and use of the method in its intended practical context, systematic and longitudinal investigation of how to attain practical viability and usefulness of such methods is limited and often restricted to small-scale demonstrations in the scientific literature. Research that strives at generating both outcome with high practical relevance and generalisable theoretical insights calls for a methodology that pays equal attention to scientific rigour and practical value. Action Design Research (ADR) represents such methodology, serving the dual mission of advancing theory while at the same time generating knowledge about how to solve organisational problems in practice. In this paper, an ADR approach to method development in a public sector organisation during a period of three and a half years is described, based on data collected through participant observation and focus group discussions. Starting off by formulating design principles guiding the method development, a number of iterative cycles of intervention in the organisational context and evaluation of the use of the method in its intended practical setting were undertaken. The paper outlines the challenges and lessons learned from this process, and shows how the final method was shaped by organisational needs and limitations to ensure practical relevance and use.